VoXED: an online XED file extractor - Cota Neto, Amadeo Tato; Dantas, Bruno Cardoso; Teixeira, Joao Marcelo Xavier Natario; Teichrieb, Veronica (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware); 2023: Anais do XX Congresso Latino-Americano de Software Livre e Tecnologias AbertasDO - 10.5753/latinoware.2023.236298, 2023)
Kinect devices are used up to this day for image capturing and video recording in many activities. These devices make it possible to capture color and depth data, crucial to many research works. Despite that, these data are stored in a xed file, in the case of the Kinect V1, that cannot be opened directly. Existing tools to extract data from these files include the Kinect Studio application and the xed extractor developed by Daniel Jackson. Although valuable tools, they require a higher computational knowledge from the user since they require either the compilation of a source code or to develop an application that uses the stored data like it was received from a Kinect device while a Kinect device is physically connected to the user’s computer. In this paper, we propose a web service that allows users to retrieve color data from xed files in an easier way than the existing tools, by retrieving a compressed file with the images stored on xed files. The obtained results show that we successfully retrieved the images stored on these files, making it possible to reuse old xed files containing important information such as body posture datasets.